Care in nursing : principles, values and skills - McSherry, Robert; McSherry, Wilfred; Watson, Roger , 1955- (Oxford University Press, 2012)
Overview: Care in Nursing addresses the fundamental caring principles, values, and skills nurses require to provide sound care to their patients and to meet the challenges of nursing in the future. Exploring essential knowledge and competencies, the authors explore research, evidence and real life practice before outlining practical skills which will empower nurses to deliver quality care. Written by nurses and health professionals from both practice and academia, Care in Nursing explores how care underpins every element of nursing including: patient centered care, cultural diversity, sociology, psychology, communication, partnership working, law and ethics, management and leadership, and more. A specific chapter also addresses how nurses can develop self-care techniques to meet the pressures and demands of a challenging yet ultimately rewarding career. Relevant to nurses in all fields and a diverse range of clinical and non-clinical settings, this is essential reading for nursing students, qualified nurses, mentors, nursing academics as well as nurse managers and leaders.